2008
DOI: 10.3390/s8106448
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Silica Optical Fibre Gratings

Abstract: A regenerated optical fibre Bragg grating that survives temperature cycling up to 1,295°C is demonstrated. A model based on seeded crystallisation or amorphisation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(126 citation statements)
references
References 4 publications
5
110
1
3
Order By: Relevance
“…To maximise the chance of the process working, the original experiments focused on strong fibre Bragg gratings written with hydrogen. The results reported in [Canning et al 2008b] verify that a new grating structure which was stable up to 1295°C before the fibre broke could be obtained. Despite the deterioration and breaking of the fibre in an open environment at such temperatures, the remaining regenerated grating remained intact when broken pieces were analysed, consistent with a stronger glass than the original glass.…”
Section: Regenerationsupporting
confidence: 64%
See 4 more Smart Citations
“…To maximise the chance of the process working, the original experiments focused on strong fibre Bragg gratings written with hydrogen. The results reported in [Canning et al 2008b] verify that a new grating structure which was stable up to 1295°C before the fibre broke could be obtained. Despite the deterioration and breaking of the fibre in an open environment at such temperatures, the remaining regenerated grating remained intact when broken pieces were analysed, consistent with a stronger glass than the original glass.…”
Section: Regenerationsupporting
confidence: 64%
“…In practice, we have confirmed that the stronger the seed grating, the stronger the final regenerated grating. For this case, a conventional Bragg grating inscribed into hydrogen loaded (24hrs, 200atm, 70°C) relatively highly germanium doped step index fibre with no boron (r core ~ 2μm, [GeO 2 ~ 10.5mol%], Δn co/cl = 0.012), using the 244nm output from a frequency doubled Ar + laser (P ~ 50W/cm 2 , f cumulative ~ (6-12)kJ/cm 2 , the same as that reported in Bandyopadhyay et al 2008 andCanning et al 2008b). Figure 6 shows the transmission and reflection of a very strong type I Bragg grating, readily exceeding the noise floor in transmission of our tunable laser and power meter setup (res: 1pm).…”
Section: Fabrication Of Seed Gratingsmentioning
confidence: 99%
See 3 more Smart Citations